EFFECT OF LIGHT INTENSITY ON CHLOROPHYLL CONTENT IN SPINACH LEAVES (Amaranthus sp.) - annisa, desti khairani nur; Dea Aulia; Desti khairani Nur Annisa; Erlina Utami; Nazwalifia Nursyifa; Mira Andriyani (Ikatan Dosen Menulis, 2025)
This research aims to determine the effect of light intensity on chlorophyll content in spinach leaves (Amaranthus sp.). Light is an essential factor in photosynthesis, directly influencing chlorophyll formation. The study was conducted using four light intensity treatments: 25%, 50%, 75%, and 100%. Chlorophyll content was analyzed using the acetone extraction method and absorbance measurement with a spectrophotometer at wavelengths of 645 nm and 663 nm. The results showed that increasing light intensity significantly affected chlorophyll content. The highest chlorophyll concentration was found at 75% light intensity (1.85 mg/g), while the lowest was at 25% (0.94 mg/g). Thus, the optimal light intensity for chlorophyll formation in spinach leaves is moderate (75%).